MODEL PEMBELAJARAN OPEN ENDED BERBANTUAN MEDIA SMARTTOON : EFEKTIVITASNYA TERHADAP KEMAMPUAN KOGNITIF MATEMATIKA PADA SISWA KELAS IV SD - Narulita Ardiningtyas; Rissa Prima Kurniawati; Elly’s Mersina Mursidik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Grade IV elementary school students have low cognitive abilities in mathematics. This low ability is caused by a lack of understanding of the material. The teacher only explains the material briefly on the board and immediately gives questions, so that students have difficulty understanding the material. This study aims to determine the effectiveness of the Open Ended learning model assisted by Smarttoon media on the cognitive abilities of mathematics in grade IV elementary school students. This study uses a quantitative approach with a True Experimental Design type Posttest Only Control Group Design. The subjects of this study were students of SDN Ngadirejo 02 with class IV A as the control class and class IV B as the experimental class. The sample in this study amounted to 37 students consisting of class IV A as many as 20 students and class IV B as many as 17 students. The sampling technique in this study was Probability Sampling using the Simple Random Sampling type. The results of the study showed that there was a significant difference in cognitive abilities between students who used the Open Ended learning model assisted by Smarttoon Media and the learning model using the lecture method. Based on the posttest results, the average experimental class was 82.65 and the control class was 65.50. Hypothesis testing was conducted using the t-test, with a significant level of 0.000 <0.05, so the Open Ended learning model assisted by Smarttoon Media on the cognitive abilities of mathematics in grade IV elementary school students is very effective to use.